Influence of caged noble-gas atom on the superatomic and valence states of C60− - Gromov, Evgeniy; Klaiman, Shachar; Cederbaum, Lorenz S. (Molecular physics, 2015)
Using high-level ab initio coupled cluster methods, we have conducted a detailed study of two endofullerene anions, HeC−60 and Ne@C−60. The main focus was on elucidating the effect of the noble-gas atom on the energy and electronic structure of the stable anion states of the parent C−60. Our study revealed that the noble-gas atom has no influence on the valence-like states of C−60, but strongly affects the superatomic-like 2Ag state. The latter was found to undergo pronounced destabilisation in both the He@C−60 and Ne@C−60 species, losing more than 70% of its original electron binding energy. The observed destabilisation is due to perturbation of the excess electron density of the 2Ag state inside the C60 cage by the caged noble-gas atom. We show how the results of our analysis can be used to predict the behaviour of the 2Ag state in other closed-shell endohedral complexes. Some possible implications of the observed features of the 2Ag state are discussed.